2022
DOI: 10.3390/ma15165754
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of ESGFIBER in Asphalt Paving Mixture

Abstract: The global desire to improve the performance of road pavements and move towards a sustainable transportation system has immensely encouraged the usage of fibers in asphalt paving materials. In this study, glass fibers trademarked as ESGFIBER produced by the ESG Industry company Limited from Daejeon, Korea were added in dense-graded asphalt mix. The purpose of this study was to evaluate effects that fibers have on volumetric properties, mechanical properties, and long-term performance of asphalt concrete mixes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…However, after the optimum content was reached, agglomeration and uneven dispersion were more likely to occur due to excessive fiber, which affected the effects of fiber in asphalt mixtures and reduced the performance improvement effect. A. Mrema et al added glass fiber to a dense-graded asphalt mixture, and the experimental investigation revealed that with the increase of glass fiber content, the indirect tensile strength initially exhibited an increase trend and then decreased [31]. Therefore, it is necessary to consider the dispersion uniformity when mixing various types of fibers into asphalt mixtures.…”
Section: Effects Of Fiber Type On Cracking Resistancementioning
confidence: 99%
“…However, after the optimum content was reached, agglomeration and uneven dispersion were more likely to occur due to excessive fiber, which affected the effects of fiber in asphalt mixtures and reduced the performance improvement effect. A. Mrema et al added glass fiber to a dense-graded asphalt mixture, and the experimental investigation revealed that with the increase of glass fiber content, the indirect tensile strength initially exhibited an increase trend and then decreased [31]. Therefore, it is necessary to consider the dispersion uniformity when mixing various types of fibers into asphalt mixtures.…”
Section: Effects Of Fiber Type On Cracking Resistancementioning
confidence: 99%